Unveiling the Potential of Ambient Air Annealing for Highly Efficient Inorganic CsPbI3 Perovskite Solar Cells - Iqbal, Zafar; Félix, Roberto; Musiienko, Artem; Thiesbrummel, Jarla; Köbler, Hans; Gutierrez-Partida, Emilio; Gries, Thomas W.; Hüsam, Elif; Saleh, Ahmed; Wilks, Regan G.; Zhang, Jiahuan; Stolterfoht, Martin; et al. (Journal of the American Chemical Society, 2024)
Here, we report a detailed surface analysis of dry- and ambient air-annealed CsPbI3 films and their subsequent modified interfaces in perovskite solar cells. We revealed that annealing in ambient air does not adversely affect the optoelectronic properties of the semiconducting film; instead, ambient air-annealed samples undergo a surface modification, causing an enhancement of band bending, as determined by hard X-ray photoelectron spectroscopy measurements. We observe interface charge carrier dynamics changes, improving the charge carrier extraction in CsPbI3 perovskite solar cells. Optical spectroscopic measurements show that trap state density is decreased due to ambient air annealing. As a result, air-annealed CsPbI3-based n-i-p structure devices achieved a 19.8% power conversion efficiency with a 1.23 V open circuit voltage.
CRIS-Team Scopus Importer:2024-03-01